Identification of Shallow Foundation In Swampland Banjarmasin - Agusniansyah, Nursyarif; Sarbini, Gusti Novi (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
The condition of the land in Banjarmasin is swamp land (commonly called soft soil) with low bearing capacity so that a special and suitable foundation is needed. This makes the uniqueness and characteristics of the foundations that are often applied in this area. The type of foundation that is often used is to follow materials such as wooden poles or concrete pillars. This is an advanced application of the shallow foundation type. In this study, an in-depth study of the types of foundations on swampy soils in Banjarmasin will be carried out in the form of types including shallow foundations. It will be investigated by comparing the field findings in the area around and outside the city of Banjarmasin. Comparison of the types of foundations found will identify how they are applied. Field observation studies were carried out at various construction sites in Banjarmasin and the surrounding area, especially objects of low-rise buildings and other uses such as fences and earthfill retaining walls. The data is presented in a descriptive manner. The purpose of this study is to provide an applicative description of the foundation in the Banjarmasin swamp land with a comparison of the types of foundations in the surrounding area. It will identify the foundation materials that can be applied and how the application techniques are implemented in the field.